Obinutuzumab induction and maintenance in patients with Waldenström macroglobulinaemia: an open-label, single-arm phase 2 studyResearch in context - Tomasz Wróbel; Elżbieta Kalicińska; Jan Maciej Zaucha; Marta Morawska; Krzysztof Giannopoulos; Krzysztof Jamroziak; Ewa Lech-Marańda; Michał Taszner; Agnieszka Szeremet; Bartosz Małecki; Agnieszka Druzd-Sitek; Anna Łojko-Dankowska; et al. (EClinicalMedicine)
Summary: Background: Despite progress in the treatment of Waldenström macroglobulinaemia, this disease still remains a therapeutic challenge, especially in older patients with multiple comorbidities. This study aimed to assess obinutuzumab single-agent induction and maintenance activity and safety in patients with relapsed or refractory Waldenström macroglobulinaemia. Methods: This open-label, single-arm phase 2 study enrolled patients with relapsed or refractory Waldenström macroglobulinaemia with confirmed CD20 expression and measurable disease. Patients received an infusion of obinutuzumab 1000 mg on days 1, 8, and 15 during first cycle, followed by five more cycles with infusions on day 1. Patients with a response defined as stable disease or better at the end of the induction phase entered 2-year maintenance treatment with obinutuzumab 1000 mg every eight weeks, followed by the observation phase. The primary endpoint was best overall response. This trial is registered at ClinicalTrials.gov, NCT03679455, and EudraCT, 2016-005053-20. Findings: Between September 04, 2018 and March 25, 2021, we enrolled 23 patients (median age 66 years, range 52–86 years). The median duration of follow-up was 3.8 years (range 0.1–6.0).The best overall response rate (BOR) was 65.2% (15 of 23 [95% CI 42.7–83.6]). In patients with baseline IgM level ≥40 g/L, BOR was reported in 75.0% (9 of 12 [95% CI 42.8–90.5]).Overall response rate (ORR) at the end of induction was reported in 12 (51%) of 23 patients. At the end of the study, ORR was reported in 15 (65%) of 23 patients. After the end of the study, the percentage of patients who achieved a very good partial response (VGPR) and complete remission (CR) has increased significantly compared to proportion of patients who achieved VGPR and CR after the 6-month induction phase (26% vs 4%, and 4% vs 0%, respectively). Progression-free survival was 65% (95% CI 43–84); overall survival was 74% (95% CI 52–90).Grade 3 or higher adverse events occurred in 15 (65.2%) patients, however, treatment-related grade 3 or higher adverse events occurred in 8 (34.8%) patients. One death that occurred during the induction phase was associated to disease progression, one death that occurred during maintenance phase was related to COVID-19, and one with disease progression. The remaining 3 deaths occurred during the follow-up phase, during subsequent lines of treatment. Interpretation: Obinutuzumab is active as single-agent induction and maintenance in patients with relapsed or refractory Waldenström macroglobulinaemia with manageable toxicity. Clinically significant is the fact that very good responses were deepened after the completion of the study with obinutuzumab. Funding: Roche Polska Ltd.